Are psychophysically chosen lifting loads based on joint kinetics?. (January 2019) - Banks, Jacob J.; Caldwell, Graham E.
Abstract: Tables of maximal acceptable weight limits (MAWL) are used to select safe lifting loads and help reduce workplace injuries. However, their subjective basis provides little information on the underlying load selection rationale, and few studies have examined MAWLs in relation to full-body joint demands. Therefore, link-segment biomechanical modeling was applied for 18 participants during three sagittal 4.3 lifts/minute tasks at chosen MAWL levels. Each lift produced unique kinematics, kinetics, MAWL loads and most highly stressed joints. Lifting from the lowest starting position most heavily challenged the L5/S1 joint, whereas more upright starting postures stressed the shoulder. Lifting loads above and below MAWL level demonstrated consistent joint loading patterns. The normalized peak moments of the highest stressed joint were similar across the lifts at ∼70–75% of the joint maximum. Our results suggest that MAWLs may be chosen based on perception of the most stressed joint for the specific lift. Highlights: Biomechanical modeling can help describe psychophysical load selection. Safe loads may be related to perceived strength of the most stressed joint. Normalized peak moments of the highest stressed joint are similar across lifts.